The Internet edge : social, legal, and technological challenges for a networked world - Stefik, Mark J. (Cambridge MA : MIT Press, 1999)
The Internet edge: change and connections. The portable network: away from the desktop and into the World. The digital wallet and the copyright box: the coming arms race in trusted systems...
Keywords: Internet; Social aspects; Computers and civilization; Information society; Internet (Computer network) -- Social aspects